Value Co-creation in Third-Party Managed Virtual Communities and Brand Equity - Rubio, Natalia; Villaseñor, Nieves; Yagüe, MªJesús (Frontiers in Psychology, 2020)
Value co-creation continues to be a key issue in the era of marketing 4.0. Despite an increasing amount of research on co-creation value, there is still a lot of ambiguity in the use of certain terms, for example, different names are used to refer to the same concept. Thus, the concept of co-innovation or co-production have nearly the same meaning as co-creation, however, there are certain differences between them that must be clarified. In addition, another of the difficulties found in the literature is that the co-creation concept is frequently applied to different objects of study, such that it might be dealing with brand value co-creation, cocreation of experience, co-creation attitude etc. In order to clarify these issues, this paper presents a brief review of the relevant literature on co-creation value.